PEREBUTAN PENGARUH MASSA DI KABUPATEN BANYUWANGI TAHUN 1960-2000 OLEH ORGANISASI MUHAMMADIYAH - Lutfiyatul Hasanah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2018)
Muhammadiyah is one of the Islamic organizations in Indonesia. The existence of Muhammadiyah in Banyuwangi creates a conflict for Muslims, especially in Banyuwangi. This relates to the existence of the NU organization which had been established earlier than the Muhammadiyah organization. The existence of the Muhammadiyah organization which was overshadowed influenced the power of NU which affected the number of masses who followed the two organizations. In its development the Muhammadiah organization became a political party. This is influenced by the condition of the community, assistance from charities, and the role of the government. This is also what indirectly becomes the influence of the masses to be in it.